Post‐COVID‐19 fatigue and anhedonia: A cross‐sectional study and their correlation to post‐recovery period - Samir El Sayed; Doaa Shokry; Sarah Mohamed Gomaa (Wiley, 2021)
Abstract Background Individuals infected by the novel coronavirus (SARS‐CoV‐2) have experienced different psychiatric manifestations during the period of infectivity and post‐COVID‐19 infection. Fatigue and anhedonia are among the frequently reported manifestations after recovery from this novel viral pandemic, leading to early evaluation of those patients and proper management of their complaints which have a drastic burden on different domains of life. Also, the period after recovery might have an effect on the severity of these two psychiatric presentations. Aim of the work This cross‐sectional observational study aimed to investigate the occurrence of post‐COVID‐19 fatigue and anhedonia and whether the duration after 2 consecutive PCR‐negative tests has an implication on the severity of the above‐mentioned psychiatric manifestations. Methods Socio‐demographic characteristics of 200 post‐COVID‐19 patients were collected, and also, the self‐assessment anhedonia scale was used to evaluate the degree of anhedonia. Fatigue assessment scale used to investigate this domain. The study targeted to find a possible correlation between the period after recovery and the other variables including anhedonia and fatigue. Results The study revealed high scores of different subtypes of self‐assessment anhedonia scale (including total intensity, total frequency, and total changes scores) in the studied group, also high score of fatigue assessment scale in those patients. Positive statistically significant correlation between anhedonia and fatigue in post‐COVID‐19 group, also negative statistically significant correlation between duration after recovery and the other 2 variables(anhedonia and fatigue) in the examined patients. Conclusion Post‐COVID‐19 fatigue and anhedonia were prevalent and commonly reported in the post‐COVID‐19 period, also the duration after 2 consecutive negative PCR tests has an implication on the severity rating scale of both anhedonia and fatigue. These findings directed our attention to those reported manifestations which affected the socio‐occupational functioning of the individuals during this whole world pandemic.